Usha Jumani. Dealing with Poverty: Self-Employment for Poor Rural Women. New Delhi/Newbury ParklLondon: Sage Publications. 1991. (The Pakistan Development Review, 1992)
Based on extensive fieldwork carried out in collaboration with SEW A, Jumani's book is a study of the issues of poor self-employed women in the rural areas of Ahmedabad District of Gujrat, India. The work and social issues of rural women working in fifteen different economic activities have been studied in depth through participatory methods as a basis of organising the women and strengthening their resource bases. The study covers five out of seven districts which are lightly rural and the sample consists of 800 poor self-employed women in 561 villages. The contents of book have been divided into two parts. Part I of the book comprises seven chapters, while Part II provides case-studies of at least two women in each activity. Chapter 1 elaborates the historical process of the economic transformation from the informal to the formal set-up of the present-day Indian economy. However, it is argued that the transformation process, contrary to the expectation that it would generate employment, has led to the expansion of the communities of the poor self-employed workers. These workers, in contrast to formal-sector workers, are denied any legal rights to work, security, earnings, etc.